Modal Kerja Dalam Keuangan Syariah - Sarani Sarani; Mila Firstika Julianti; Esi Arjuna Arjuna (Proceeding International Seminar of Islamic Studies, 2019)
: Working capital in Islamic finance basically, capital is not only in the form of money, but assets that are used for business purposes for dynamic turnover. working capital in general has a lower financial level compared to fixed asset investment. Because of that small working capital will further enhance the company. conversely, working capital that is too small will increase the risk of the company (especially liquidity risk). from a risk standpoint, higher working capital will benefit the company, because the risk is lower. and there are some imperfect conditions that make working capital decisions important, namely, transaction costs where transaction costs include two types namely explicit and implicit costs, and asynchronous activity. then working capital in Islamic finance is current capital that is used to support the company's daily operations so that the company can operate normally and smoothly.